A gestão escolar no município de Amélia Rodrigues: os mecanismos democráticos em disputa - Martins, Dejane Ribeiro (2018)
This research presents an analysis of the trajectory of the election for school administrators in the municipal network of Amélia Rodrigues from the official documents from 2000 to 2010. The year 2000 was the initial milestone of the regulation and the year 2010 was published the first public notice after change of government. In this sense, this research has as object of study the conceptions about school management evidenced in the trajectory of the election for school managers in the city of Amélia Rodrigues-BA, and as a guiding question: How are the conceptions about school management evidenced in the trajectory of the election for school managers in the municipality of Amélia Rodrigues from 2000 to 2010? The general objective was to analyze the conceptions about school management evidenced in the trajectory of the election for school managers in the municipality of Amélia Rodrigues-BA. Thus, the research refers to school management based on a democratic perspective, committed to the promotion of citizenship, and social emancipation, as opposed to the managerial aspect of public administration. With regard to the research instruments, the analysis of the documents that regulated the election for municipal school managers and semi-structured interviews was used. In order to do so, it sought to know in the municipal scope the guiding documents that directly related to the school management, the instruments and instances that operationalize the democratic management in the schools of the municipal network, as well as the characteristics and conceptions evidenced in the legal documents. The analysis of the data, gathered in the documents and the interviews, was based on the approach of the Policy Cycle (context of influence and practice) based on the work of Stephen Ball and Richard Bowe, English researchers in the area of educational policy. Thus, we adopt a theoretical basis based on the studies of authors such as: Bobbio (2000); Coutinho (2002); Paro (1998); Frigotto, Ciavatta (2003); Cury (2002); Sander (2005); Luck (2006) among others. The data of this investigation revealed that there are many barriers regarding the true participation of the different segments in the management of the school. Therefore, although there is considerable progress regarding collective participation in school units with the election of school administrators, there is still a lot to be done, so that school democratization becomes a reality in the municipality of Amélia Rodrigues.